Lembaga Tabung Haji / Nur Mastura Mohamed Noor - Mohamed Noor, Nur Mastura (Universiti Teknologi MARA, Perlis, 2023)
This internship report focuses on the work experienced that I have gained during my six-month industrial training at Lembaga Tabung Haji. In this report I have included my experience at Tabung Haji especially on Hajj, marketing, finance, and administration. I worked at Tabung Haji branch that require multitasking. I also provide my details job description where I had to work with different roles. The objective of this report is to identify and learn internal strengths and weaknesses, and external opportunities and threats that affect the organization. SWOT analysis will help identify and develop improvement for an organization. To be excellent in Hajj pilgrimage management and expending investment, recommendations are needed as an option to be adapted. This report will incorporate the advantages of opportunities, overcoming weakness, and minimizing threats.